Morphological phenotyping after mouse whole embryo culture - Copp, Andrew J.; Clark, Maryam; Greene, Nicholas D. E. (Frontiers in Cell and Developmental Biology, 2023)
Morphological phenotyping of the mouse embryo is described at neurulation stages, primarily as a guide to evaluating the outcome of whole embryo cultures between embryonic days 8.5 and 9.5. During this period, neural tube closure is initiated and progresses to completion in the cranial region. Spinal closure is still underway at the end of the culture period. The focus of this article is particularly on phenotyping that can be performed at the bench, using a stereomicroscope. This involves assessment of embryonic health, through observation and scoring of yolk sac blood circulation, measurement of developmental stage by somite counting, and determination of crown-rump length as a measure of growth. Axial rotation ('turning') can also be assessed using a simple scoring system. Neural tube closure assessment includes: (i) determining whether closure has been initiated at the Closure 1 site; (ii) evaluating the complex steps of cranial neurulation including initiation at Closure sites 2 and 3, and completion of closure at the anterior and hindbrain neuropores; (iii) assessment of spinal closure by measurement of posterior neuropore length. Interpretation of defects in neural tube closure requires an appreciation of, first, the stages that particular events are expected to be completed and, second, the correspondence between embryonic landmarks, for example somite position, and the resulting adult axial levels. Detailed embryonic phenotyping, as described in this article, when combined with the versatile method of whole embryo culture, can form the basis for a wide range of experimental studies in early mouse neural development.